On the identity of Thespis disparilis Westwood, 1889 (Mantodea: Mantidae: Mantinae) - Milledge, Graham A.; Ehrmann, Reinhard (Zootaxa, 2014)
Thespis disparilis was described by Westwood (1889) from a male and a female specimen collected from Swan River in Australia. Swan River was the colony that eventually became Perth, the capital city of the state of Western Australia. Westwood’s description was brief, in Latin and no illustrations were provided. The type specimens are deposited in The Hope Entomological collections, University Museum, Oxford, England.